(untitled) (Journal of the College of Basic Education, 2022)
The size of the population is one of the most important elements of the consumer function, as the imbalance betweenConsumption on the one hand and production and productive resources on the other hand can lead to impossibilityFood security plans. The high percentage of urban growth in Iraq for the period2011-7 indicates that migration from rural to urban areas is still continuing due to stumblingAgricultural development policies and programmes. This is in addition to the increased demand for food as a result of the changeurban lifestyle, which further complicated the problem of food security; Hence the probability of occurrenceviolence. Galtung Asnalah6 referred to three forms of violence as a result of hunger and povertyworld wide thereof